The interrelation between socio-cultural aspects and the quality of public open spaces in Almaty, Kazakhstan - Anuar, Aznamkhan; Mekhribanu, Glaudinova; Abdullah, Alias (Malaysian Institute of Planners, 2024)
This article investigates how socio-cultural factors impact the quality of public open spaces (POS) in Almaty. The study's relevance lies in the significant role public spaces play in local and citywide contexts, as well as in architectural and urban planning policies. Jan Gehl highlighted how urban environments and planning decisions shape city behaviour, emphasizing the global importance of urban space development. Jacobs developed methods to model social interactions with a focus on environmental safety, while Campbell explored social boundaries, and Lynch and Jacobs examined the socio-cultural aspects influencing POS formation. The research employs an interdisciplinary methodology, analysing Almaty's socio-cultural context, POS design, and functioning. Surveys among residents were conducted to gauge their perceptions of these spaces. The study spans urban planning, sociology, cultural studies, and landscape architecture, using both qualitative and quantitative methods, including photo documentation, sociological research, and mathematical modelling of selected POS sites. The findings reveal that the quality of POS in Almaty is influenced by their appeal to social groups, the availability of cultural events, and the levels of safety and comfort. These factors are crucial for creating inviting and functional public spaces. The study's results aim to guide future improvements in open public spaces, not only in Kazakhstan but also in other developing countries.